2021
DOI: 10.3390/molecules26195830
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of a Thermostable Carbonic Anhydrase in Escherichia coli by Using a Modified NEXT Tag

Abstract: Carbonic anhydrase (CA) is an ultrafast enzyme that catalyzes the reversible conversion of carbon dioxide (CO2) to bicarbonate. CA is considered to be a green catalyst for enzyme-based CO2 capture and utilization. In particular, the CA of Thermovibrio ammonificans (taCA) has attracted increasing attention as a highly stable enzyme. However, the poor solubility and the low expression level in Escherichia coli have hampered further utilization of taCA. In a recent study, these limitations were partly resolved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…coli and S. cerevisiae, such as NEXT, MBP, and Ser-Lys-Ile-Lys (SKIK) . To improve the expression of GfCPS/KS without losing its activity, a series of short peptide tags (SK, SKI, and SKIK) were inserted into the N-termination of GfCPS/KS, resulting in strains JR15–17.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…coli and S. cerevisiae, such as NEXT, MBP, and Ser-Lys-Ile-Lys (SKIK) . To improve the expression of GfCPS/KS without losing its activity, a series of short peptide tags (SK, SKI, and SKIK) were inserted into the N-termination of GfCPS/KS, resulting in strains JR15–17.…”
Section: Resultsmentioning
confidence: 99%
“…Production by Enzyme Engineering. It has been reported that some peptide tags could markedly improve the expression level of proteins in E. coli and S. cerevisiae, such as NEXT, 36 MBP, 37 and Ser-Lys-Ile-Lys (SKIK). 38 To improve the expression of GfCPS/KS without losing its activity, a series of short peptide tags (SK, SKI, and SKIK) were inserted into the N-termination of GfCPS/KS, resulting in strains JR15−17.…”
Section: Improving the Ent-kaurenementioning
confidence: 99%
“…coli with minimal or no impact on enzyme activity [ 32 ]. Tag systems such as MBP (maltose binding protein) [ 33 ] and NEXT (originating from N-terminus of Hydrogenovibrio marinus CA) [ 34 ] are widely used. NEXT tag was shown to increase the soluble expression level in E. coli BL21 (DE3) by up to 5.6–8.3 fold [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NEXT tag has been employed as a fusion tag to address the challenges associated with both the low-level expression and poor solubility of taCA [18,19]. The NEXT tag, a 53 amino acid-length peptide with a molecular mass of 5.5 kDa, originated from the N-terminal extension sequence of α-type CA (hmCA) in the marine bacterium Hydrogenovibrio marinus [18,20].…”
Section: Introductionmentioning
confidence: 99%